ANALYSIS OF PROSPECTS FOR INCREASING ECONOMIC AND LEGAL LITERACY IN PUBLIC LIFE (Scientific Conference on Multidisciplinary Studies, 2025)
This research analyzes the prospects for improving economic and legal literacy within society, focusing on statistical data from 2022 to 2024. In 2022, only 45% of adults demonstrated a basic understanding of economic principles, while legal literacy was reported at a mere 38%, according to the National Literacy Survey. Projections for 2023 indicate a slight improvement, with expected increases to 50% for economic literacy and 42% for legal literacy, driven by enhanced educational programs and community outreach initiatives. By 2024, these figures are anticipated to rise further to approximately 55% and 48%, respectively, as digital platforms and interactive learning tools become more prevalent in educational curricula. This upward trend underscores the critical need for sustained investment in educational resources and public awareness campaigns aimed at fostering a more informed citizenry capable of making sound economic decisions and understanding their legal rights.